International matching grant MoA signing ceremony between UiTMCK and Mae Fah Luang University (MFLU), Thailand and Universitas Gadjah Mada, Indonesia (UGM) - UiTM Cawangan Kelantan, Unit Komunikasi Korporat (2022)
MACHANG, 7 November - UiTM Cawangan Kelantan (UiTMCK) has hosted the International Matching Grant MoA signing ceremony between UiTMCK and Mae Fah Luang University (MFLU), Thailand and Universitas Gadjah Mada, Indonesia (UGM) on the 2nd of November 2022 (Wednesday). The ceremony was chaired by Prof. Dr Haji Abdol Samad Nawi, Rector of UiTMCK and participated by the top management of UiTMCK. MFLU Thailand was represented by Dr Piyatida Pianluprasidh, Dean of the School of Management and Assistant Professor Dr Dej-anan Bungkilo, Associate Dean of the School of Management. While UGM Indonesia was represented by Professor Dr Didi Achjari, Dean of the Faculty of Economics and Business, Dr Gumilang Aryo Sahadewo, Vice Dean of Research, Community Services, Cooperation, and Alumni of the Faculty of Economics and Business and Professor Dr Nurul Indarti, Project Leader, Head of Department of Management, Faculty of Economics and Business.